Closing the gender data gap. Issue 2 (April 2016) - Buvinic, Mayra; Levine, Ruth
Abstract : World leaders have committed to gender equality with the Sustainable Development Goals, but we currently lack the data that is required to ensure this target is met, say Mayra Buvinic and Ruth Levine Abstract : World leaders have committed to gender equality with the Sustainable Development Goals, but we currently lack the data that is required to ensure this target is met, sayMayra Buvinic andRuth Levine